Impact of severe ADAMTS13 deficiency on clinical presentation and outcomes in patients with thrombotic microangiopathies: the experience of the Harvard TMA Research Collaborative. (28th August 2015) - Bendapudi, Pavan K.; Li, Ang; Hamdan, Ayad; Uhl, Lynne; Kaufman, Richard; Stowell, Christopher; Dzik, Walter; Makar, Robert S.
Summary: The Harvard TMA Research Collaborative is a multi‐institutional registry‐based effort to study thrombotic microangiopathies (TMA). Laboratory and clinical parameters were recorded for 254 cases of suspected autoimmune thrombotic thrombocytopenic purpura (TTP). Patients with severe ADAMTS13 deficiency (activity ≤10%, N  = 68) were more likely to be young, female and without a history of cancer treatment or transplantation. While all patients with severe deficiency were diagnosed with autoimmune TTP, those without severe deficiency frequently had disseminated intravascular coagulation, drug‐associated TMA and transplant‐related TMA. Patients with severe ADAMTS13 deficiency had superior overall survival at 360 d compared to those without severe deficiency (93·0% vs. 47·5%, P  < 0·0001). Almost all patients with severe deficiency received therapeutic plasma exchange (TPE), but the use of TPE in patients with ADAMTS13 activity >10% varied significantly across the institutions in our consortium (13·2–63·8%, P  < 0·0001). Nevertheless, 90‐d mortality was not different in patients with ADAMTS13 activity >10% between the three hospitals ( P  = 0·98). Our data show that patients with severe ADAMTS13 deficiency represent a clinically distinct cohort that responds well to TPE. In contrast, TMA without severe ADAMTS13 deficiency is associated with increased mortality that may not be influenced by TPE.